Pengaplikasian Face Recognition 3 Dimensi Untuk Keamanan - Jason Adrian Mahalim; Muhamad Aliefian Rahmatulloh; Muhamad Rizky Febrianto; Nabila Husna Shabrina (Ultima Computing : Jurnal Sistem Komputer, 2020)
Face recognition is one of the biometric categories which uses face as the identifier. Currently, there are two versions of face recognition, 2 dimensional and 3 dimensional. This research uses 3 dimensional face recognition, and the goal for this research is for comparing the accuracy between 2 dimensional and 3 dimensional face recognition, analyze the performance of 3 dimensional face recognition, and applying 3dimensional face recognition for security measure, namely for automatic door lock using face recognition. Face Alignment Network used as the method for this 3 dimensional face recognition. This research prove that 3 dimensional face recognition have better accuracy than its predecessor, however some weakness is also found in this research, i.e. image resolution, lighting of the photo, angle of the face when the photo taken will govern the accuracy of the 3 dimensional face recognition and 3 dimensional face recognition can’t differentiatebetween twins brother faces.Key word : Face recognition, accuracy